2012
DOI: 10.4049/jimmunol.1003939
|View full text |Cite
|
Sign up to set email alerts
|

A Novel NKR-P1Bbright NK Cell Subset Expresses an Activated CD25+CX3CR1+CD62L−CD11b−CD27− Phenotype and Is Prevalent in Blood, Liver, and Gut-Associated Lymphoid Organs of Rats

Abstract: The inhibitory NKR-P1B receptor identifies a subset of rat splenic NK cells that is low in Ly49 receptors but enriched for CD94/NKG2 receptors. We report in this study a novel NKR-P1Bbright NK subpopulation that is prevalent in peripheral blood, liver, and gut-associated lymphoid organs and scarce in the spleen, peripheral lymph nodes, bone marrow, and lungs. This NKR-P1Bbright NK subset displays an activated phenotype, expressing CD25, CD93, CX3CR1 and near absence of CD62-L, CD11b, and CD27. Functionally, NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…This pattern is suggestive of subsets differentially regulated by MHC-I-dependent and MHC-I-independent recognition mechanisms. In addition, further characterization has revealed Nkrp1b to be highly expressed by unique subset(s) of circulating and liver/gut-resident lymphocytes, some of which may include mature/activated NK cells and/or ILC-like cells; these cells are enriched for CD8α, CD25, CD93, CX 3 CR1, but depleted for CD62L, CD27, and CD11b (90). Interestingly, Nkrp1g transcripts are exclusively expressed in the Ly49s3 + subset, while Nkrp1f is expressed in both subsets (22).…”
Section: Expressionmentioning
confidence: 99%
“…This pattern is suggestive of subsets differentially regulated by MHC-I-dependent and MHC-I-independent recognition mechanisms. In addition, further characterization has revealed Nkrp1b to be highly expressed by unique subset(s) of circulating and liver/gut-resident lymphocytes, some of which may include mature/activated NK cells and/or ILC-like cells; these cells are enriched for CD8α, CD25, CD93, CX 3 CR1, but depleted for CD62L, CD27, and CD11b (90). Interestingly, Nkrp1g transcripts are exclusively expressed in the Ly49s3 + subset, while Nkrp1f is expressed in both subsets (22).…”
Section: Expressionmentioning
confidence: 99%
“…We previously identified a subset of rat NK cells lacking expression of both NKR-P1B and Ly49 receptors. That subset is present in all tissues, and we showed that, in the blood, the subset was hyporesponsive in terms of IFN-g production and cytotoxicity [22]. Here, we have characterized that subset further and show that its functional capacity is linked to induced expression of NKR-P1B.…”
Section: Introductionmentioning
confidence: 66%
“…1E). The discrepancy between the degranulation and cytotoxicity assays for the Ly49s3 + subset was unexpected because we previously showed similar levels of perforin and granzyme B and the cytotoxic ability of blood-derived Ly49s3 + and NKR-P1B + subsets [22].…”
Section: Nkr-p1b 2 Ly49s3 2 Nk Cells Are Hyporesponsivementioning
confidence: 86%
See 2 more Smart Citations